Injury risks of heading in young football players - Lukasek, M.; Kalichova, M. (Journal of Human Sport & Exercise, 2015)
The aim of the research is to contribute to findings concerning increasingly acute problems connected with heading in football. Unlike most of available studies where heading with adults is dealt with, our study focuses primarily on heading with children. 16 children aged 10, weighing 36.2 ± 4.7 kg took part in the research. Each tested person executed headings of a ball dropped from 0 m (3.13 m/s), 1 m (4.43 m/s) and 1,5 m (5.43 m/s) ie. 3 headings in total. The total number of tests was 48. A triaxial accelerometer (1000 Hz) was used in the measurements. As presumed, with increasing drop-height the head acceleration increased on impact. With drop-height of 0.5 m we recorded 59.4±15.8 m·s-2, with 1 m we measured 76.4±15 m·s-2 and 100.1±25 m·s-2 from 1.5 m. These acceleration values do not pose danger if individual, however, we came to conclusion that repeated impacts, especially those of higher speed, may lead to functional problems of a child's brain.